2020
DOI: 10.1039/d0ra07679a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid membrane interactions of self-assembling antimicrobial nanofibers: effect of PEGylation

Abstract: Wrane interaction of a series of self-assembling antimicrobial peptides with and without PEGylation using small angle X-ray and neutron scattering and neutron reflectometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Very recently, Nielsen et al investigated the membrane interaction of 3W62 and P-3W62 on supported lipid bilayers by using neutron reflectometry (NR). [216] In agreement with the findings of Xu et al, assembled 3W62 filaments showed markedly stronger interaction with the model membranes than unimeric 3W32 molecules. The filaments apparently adhered to the charged lipid headgroups by electrostatic interaction with the Lysine residues at the short edge of the filament  compare Figure 1.8.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Very recently, Nielsen et al investigated the membrane interaction of 3W62 and P-3W62 on supported lipid bilayers by using neutron reflectometry (NR). [216] In agreement with the findings of Xu et al, assembled 3W62 filaments showed markedly stronger interaction with the model membranes than unimeric 3W32 molecules. The filaments apparently adhered to the charged lipid headgroups by electrostatic interaction with the Lysine residues at the short edge of the filament  compare Figure 1.8.…”
Section: Introductionsupporting
confidence: 90%
“…We furthermore aimed to transfer our fundamental knowledge gained from these model systems to more complex, biologically relevant systems. self-assembled structure of 3W62 antimicrobial peptides and their molecular exchange (Paper V), while we studied the interaction of the peptide filaments with model membranes [216] in parallel. This chapter is organized as follows: First, Papers I to V will be summarized briefly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The charge density of self-assembled peptides at the bacterial membrane surface and the charge-to-surface area ratio are the crucial factors deciding optimal membrane interactions, enabling the detergent-like effect, forming membranous pores leading to bacterial death. 36,37 Thakur and co-workers have reported the antibacterial effect of Fmoc-F hydrogels against Staphylococcus aureus and MRSA. The antibacterial potency was due to the release of solubilized Fmoc-F fragments from the hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Some naturally occurring antimicrobial peptides, modified structurally to include a selfassembling sequence, have demonstrated reduced antimicrobial activity upon self-assembling. 22 For self-assembled peptide aggregates, charge density at the assembled surface and charge to surface area ratio are important additional considerations for membrane interactions, 32,33 enabling detergent-like effect, 34 and formation of membranous pores. 35 For amphipathic antimicrobial peptides in aqueous environments, charged residues (e.g.…”
Section: Peptide-membrane Interactionsmentioning
confidence: 99%